Chronic illness burden and quality of life in an aging HIV population - Balderson, Benjamin H. (Taylor & Francis, 2012)
The population of persons living with HIV (PLWH) is growing older and more prone to developing other chronic health conditions. Disease progression has been shown to be related to quality of life (QoL). However, descriptions of chronic comorbid illnesses and the unique QoL challenges of older adults living with HIV are not well understood and have not been examined in multiple geographic locations. About 452 PLWH aged 50 years or older were recruited from AIDS Service Organizations in nine states. Participants completed a telephone survey that included measures of other chronic health conditions, perceived stress, depression, and health-related quality of life. As much as 94% of the sample reported a chronic health condition in addition to HIV (mode = 2). The highest reported conditions were hypertension, chronic pain, hepatitis, and arthritis. Despite relatively high rates of depression, overall QoL was moderately high for the sample. Physical functioning was most impacted by the addition of other chronic health problems. Social functioning, mental health functioning, stress, and depression were also strongly associated with chronic disease burden. Additional chronic health problems are the norm for PLWH aged 50 years and older. QoL is significantly related to the addition of chronic health problems. As increasing numbers of PLWH reach older age, this raises challenges for providing comprehensive healthcare to older PLWH with multiple chronic conditions.